Controversy over the Existence of the World Volume II - Hartman, Jan; Hartman, Jan; Ingarden, Roman; Szylewicz, Arthur (Peter Lang, 2019)
Roman Ingarden (1893?1970), one of Husserl's closest students and friends, ranks among the most eminent of the first generation of phenomenologists. His magisterial Controversy over the Existence of the World, written during the years of World War II in occupied Poland, consists of a fundamental defense of realism in phenomenology. Volume II, which follows the English translation of Volume I from 2013, provides fundamental analyses in the formal ontology of the world and consciousness as well as final arguments supporting the realist solution. Ingarden's monumental work proves to be his greatest accomplishment, despite the fact that outside of Poland Ingarden is known rather as a theoretician of literature than an ontologist. The most important achievement of Ingarden's ontology is an analysis of the modes of being of various types of objects ? things, processes, events, purely intentional objects and ideas. The three-volume Controversy is perhaps the last great systematic work in the history of philosophy, and undoubtedly one of the most important works in 20th-century philosophical literature. The book proves to be a classical work in the history of modern philosophy, especially in ontological phenomenology and ontology. At the same time, Ingarden$1 (Bs major work provides classical argumentation in favor of realism in philosophy. It is the most eminent achievement in the history of Polish philosophy.s